2018
DOI: 10.1093/aje/kwy086
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Acetaminophen and Risk for Attention Deficit Hyperactivity Disorder and Autistic Spectrum Disorder: A Systematic Review, Meta-Analysis, and Meta-Regression Analysis of Cohort Studies

Abstract: Acetaminophen is the most commonly used analgesic and antipyretic during pregnancy. Evidence of neuro-disruptive properties is accumulating. Therefore, we sought to evaluate the risk for attention deficit hyperactivity disorder (ADHD) and autistic spectrum disorder (ASD) in the offspring of women exposed to acetaminophen during pregnancy. We searched MEDLINE, EMBASE, and Cochrane up to January 2017. Data were independently extracted and assessed by two researchers. Seven eligible retrospective cohorts included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
73
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 51 publications
13
73
0
Order By: Relevance
“…Our results are consistent with previous studies that reported associations of acetaminophen in pregnancy with greater childhood executive function and behaviour problems . Studies in Spain, New Zealand, United Kingdom, Denmark, and Norway have reported associations of prenatal acetaminophen use with offspring behavioural problems, symptoms of attention deficit/hyperactivity disorder, and diagnosis with an autism spectrum disorder at school age.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are consistent with previous studies that reported associations of acetaminophen in pregnancy with greater childhood executive function and behaviour problems . Studies in Spain, New Zealand, United Kingdom, Denmark, and Norway have reported associations of prenatal acetaminophen use with offspring behavioural problems, symptoms of attention deficit/hyperactivity disorder, and diagnosis with an autism spectrum disorder at school age.…”
Section: Discussionsupporting
confidence: 93%
“…In a 2018 meta‐analysis of 7 studies including 132 738 participants, prenatal exposure to acetaminophen was associated with a 20%‐30% increase in the risk of neurodevelopmental disorders, including attention deficit hyperactivity disorder, autism spectrum disorders, and hyperactivity symptoms . However, there was evidence of heterogeneity between study estimates of the outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, misuse of the drug misoprostol—a PGE2 analogue—for the termination of pregnancy was linked to elevated risk of ASD . We also previously reported that PGE2 signaling in the developing brain is especially vulnerable to various environmental insults such as inflammation, oxidative stress, pollution, heavy metals, pesticides and commonly used over‐the‐counter drugs like acetaminophen and nonsteroidal anti‐inflammatory drugs including acetylsalicylic acid, which all have been linked to ASD …”
Section: Introductionmentioning
confidence: 97%
“…44 We also previously reported that PGE2 signaling in the developing brain is especially vulnerable to various environmental insults such as inflammation, oxidative stress, pollution, heavy metals, pesticides and commonly used over-the-counter drugs like acetaminophen and nonsteroidal anti-inflammatory drugs including acetylsalicylic acid, which all have been linked to ASD. [19][20][21]45 Emerging molecular evidence offers insight into possible mechanisms by which abnormal COX2/PGE2 signaling may affect brain development and lead to autism. For example, in vitro studies in our laboratory have shown that elevated levels of PGE2 can modify intracellular calcium dynamics and increase neural proliferation, migration and differentiation in neural stem cells and differentiating neurons.…”
mentioning
confidence: 99%